Cost-effectiveness of solifenacin compared with oral antimuscarinic agents for the treatment of patients with overactive bladder in the UK - Hakimi, Zalmai (J Mark Access Health Policy, 2018)
Objective: To evaluate the cost-effectiveness of solifenacin 5 mg/day versus other oral antimuscarinic agents used for overactive bladder (OAB) from a UK National Health Service (NHS) perspective. Study design: In a Markov model, hypothetical patients received solifenacin 5 mg/day or a comparator antimuscarinic, after which they could switch to an alternative antimuscarinic. The model estimated incremental cost-effectiveness ratios (ICER), expressed as cost per quality-adjusted life year (QALY) over a 5-year period. Results: Solifenacin 5 mg/day was the dominant treatment strategy (i.e., less costly and more effective) versus tolterodine extended-release (ER) 4 mg/day, fesoterodine 4 and 8 mg/day, oxybutynin ER 10 mg/day and solifenacin 10 mg/day, and was cost-effective (i.e., ICERs below the £30,000 per QALY threshold generally applied in the NHS) versus oxybutynin immediate release (IR) 10 mg/day, tolterodine IR 4 mg/day and trospium chloride 60 mg/day. The probability of solifenacin 5 mg/day being dominant/cost-effective at a willingness-to-pay threshold of £30,000 per QALY was 57–98%. Conclusions: Solifenacin 5 mg/day appears to be a cost-effective strategy for the treatment of OAB over a 5-year timeframe compared with other oral antimuscarinic agents in the UK. These findings are important for decision-makers considering the economic implications of selecting treatments for OAB.